Análisis estático y modal de barcaza de 02 bombas verticales y propuestas de reforzamiento en zonas con bajo factor de seguridad - Negreiros Polo, Jefferson Homero (2023)
The main objective of the research "Static and modal analysis of the barge of 02 vertical pumps and reinforcement proposals in areas with low safety factor" is to identify and reinforce the areas of low resistance, both in deformation and resistance and also in resonance, of the barge structure of 02 vertical pumps. The analysis showed areas with low safety factor, being necessary to reinforce and/or change parts. Subsequently, after the reinforcement, final analyses were made, where it can be seen that the reinforcements mitigated the problem and provided a solution to any event in operation. The safety factors increased, giving reliability to the design